Narratives in the Immediate Aftermath of Traumatic Injury: Markers of Ongoing Depressive and Posttraumatic Stress Disorder Symptoms. Issue 2 (6th April 2018) - Booker, Jordan A.; Graci, Matthew E.; Hudak, Lauren A.; Jovanovic, Tanja; Rothbaum, Barbara O.; Ressler, Kerry J.; Fivush, Robyn; Stevens, Jennifer
Abstract: In this study, we considered connections between the content of immediate trauma narratives and longitudinal trajectories of negative symptoms to address questions about the timing and predictive value of collected trauma narratives. Participants ( N = 68) were individuals who were admitted to the emergency department of a metropolitan hospital and provided narrative recollections of the traumatic event that brought them into the hospital that day. They were then assessed at intervals over the next 12 months for depressive and posttraumatic symptom severity. Linguistic analysis identified words involving affect (positive and negative emotions), sensory input (sight, sound, taste, touch, and smell), cognitive processing (thoughts, insights, and reasons), and temporal focus (past, present, and future) within the narrative content. In participants' same‐day narratives of the trauma, past‐focused utterances predicted greater decreases in depressive symptom severity over the next year, d = −0.13, whereas cognitive process utterances predicted more severe posttraumatic symptom severity across time points, d = 0.32. Interaction analyses suggested that individuals who used fewer past‐focused and more cognitive process utterances within their narratives tended to report more severe depressive and posttraumatic symptom severity across time, d s = 0.31 to 0.34. Overall, these findings suggest that, in addition to other demographics and baseline symptom severity, early narrative content can serve as an informative marker for longitudinal psychological symptoms, even before extensive narrative processing and phenomenological meaning‐making have occurred.